2016
DOI: 10.1021/acsami.6b02216
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Alignment of One-Dimensional Conjugated Polymer Nanocrystallites for High-Mobility Organic Field-Effect Transistors

Abstract: Controlling the morphology of polymer semiconductors remains a fundamental challenge that hinders their widespread applications in electronic and optoelectronic devices and commercial feasibility. Although conjugated polymer nanowires (NWs) are envisioned to afford high charge-carrier mobility, the alignment of preformed conjugated polymer NWs has not been reported. Here, we demonstrate an extremely simple and effective strategy to generate well-aligned arrays of one-dimensional (1D) polymer semiconductors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 38 publications
(200 reference statements)
2
110
2
Order By: Relevance
“…Egap et al and Reichmanis et al prepared ordered P3HT nanowires almost simultaneously by offering a shear force during the film forming process . Figure A shows the schematic diagram of nanowire films deposited on an FET device substrate with a shear force . Egap et al found that P3HT nanowires achieved the best order when the shearing speed was approximately 2 mm/s, as shown in Figure B.…”
Section: Device Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Egap et al and Reichmanis et al prepared ordered P3HT nanowires almost simultaneously by offering a shear force during the film forming process . Figure A shows the schematic diagram of nanowire films deposited on an FET device substrate with a shear force . Egap et al found that P3HT nanowires achieved the best order when the shearing speed was approximately 2 mm/s, as shown in Figure B.…”
Section: Device Applicationmentioning
confidence: 99%
“…Thus, the mobility of nanowire film TEF is much lower than that of single crystal or nanowire FET. Egap et al and Reichmanis et al prepared ordered P3HT nanowires almost simultaneously by offering a shear force during the film forming process . Figure A shows the schematic diagram of nanowire films deposited on an FET device substrate with a shear force .…”
Section: Device Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, two strategies have been proposed to solve this problem. Experiments demonstrated that the formation of a proper amount of preaggregates leads to less relaxation behavior and that an external force could align these aggregates and maintain this structure, which could further grow during the film drying process . However, this strategy encounters problems in that the orientation direction of the final film is determined by the long axis of the preaggregates or nanofibers, and the aspect ratio and chain mobility are decreased by the formation of aggregates .…”
Section: Liquid Crystallinity State Assisted Morphology Controlmentioning
confidence: 99%
“…Ideally, an influential design variable should be able to be varied independently from other process conditions. Recent advances in blade and shear coating techniques, currently not captured by the database, offer a promising approach to independently control the film thickness to explore its impact on charge carrier mobility [49,50].…”
Section: Film Thicknessmentioning
confidence: 99%